Teaching Engineering Mechanics by Understanding Student Learning Styles and Methods - Kristianto, Anang (Jurnal Teknik Sipil, 2005)
The important thing in teaching besides mastering the material to be taught is how well. The two things above are closely related, how to deliver the right material is very dependent on how the style and way of learning of students who listen to it. Learning styles explain individual differences to more effectively learn a concept, based on learning styles there are groups of ES (Extroversion Sensing), IS (Introversion Sensing), EN (Extroversion Intuition), IN (Introversion Intuition). In addition to Learning Styles, there is also the term Learning Ways, which shows the different ways that individuals absorb and understand information optimally. Learning styles are known as Visual, Auditory and Kinesthetic. Research on students of the Civil Engineering Department of U.K. Maranatha class of 2003 shows the tendency of learning styles ES, EN, IS, IN respectively 41.38%, 34.48%, 6.9%, 17.24%, while the majority of learning styles are Visual (68.97%) then Auditory (20.69%) and Kinesthetic (10.34%). This study concludes that most students show the tendency of ES learning style (41.38%) with the characteristics of easy learning with application and realistic. While the way of learning is dominated by Visual shows that students will capture and understand more information through what is seen. Hasil peneltian ini dapat memberikan informasi untuk mengajar Mekanika Rekayasa dengan tepat yaitu melalui simulasi, studi kasus/aplikasi , diskusi kelompok kecil serta memberikan banyak gambar menarik dan warna untuk menjelaskan materi/rumus yang diberikan. Cara mengajar yang cenderung satu arah dan menonjolkan banyak rumus daripada visualisasi yang menarik tampaknya harus ditinggalkan sehingga diharapkan mahasiswa akan menikmati pelajaran Mekanika Rekayasa dan tentunya hal ini akan berdampak pada hasil akhir yang didapat.